Lichen planus-lupus erythematosus overlap syndrome - Marina Yu. Nikolaeva; Konstantin N. Monakhov; Evgeny V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2022)
The combination of lichen planus and lupus erythematosus is a rarity: no more than fifty cases of overlap syndrome have been described in the world. The clinical picture of overlap syndrome is variable: patients have discoid foci of lupus erythematosus and typical flat polygonal papules of lichen planus, as well as combined manifestations in the form of lid-red plaques with central atrophy and superficial desquamation. Positive antinuclear factor is found in laboratory examination. The histopathological picture is characterized by a combination of histological signs of lichen planus and lupus erythematosus. In some cases, clinical and immunological signs of systemic lupus erythematosus are found in patients with overlap syndrome. We describe two cases of lichen planus and systemic lupus erythematosus.